دراسة مقارنة للنتائج الوظيفية القريبة لعلاج الفصال العظمي بمفصل الركبة باستخدام التثقيب العظمي واستخدام الليزر المفصلي - علي, ناظم (Latakia University Journal -Medical Sciences Series, 2019)
The study presents a comparison between two methods of treatment of osteoarthritis of the knee in arthroscopy, Comparison between traditional method of perforation and method with the help of laser. The study included 40 cases, 20 of which were treated in one way. The nearby functional results were evaluated after surgery, The researcher reached the following results : Laser treatment for cases of osteoarthritis of the knee is better in surgical time ,The duration of hospital stay, postoperative pain relief, reduced knee hemarthrosis , and Improved walking ability, as well as a marked decrease in the time of the discontinuity of the work. يقدم البحث مقارنة بين طريقتين لعلاج لعلاج الفصال العظمي [التنكس المفصلي] بمفصل الركبة باستخدام التثقيب العظمي واستخدام الليزر المفصلي,حيث شملت الدراسة 40 حالة كل عشرين منها عولجت بطريقة واحدة وتم تقييم النتائج القريبة بعد الجراحة وتوصل الباحث لنتائج أهمها: قدم العلاج بالليزر المفصلي لحالات الفصال العظمي أفضلية من ناحية وفرة زمن العمل الجراحي و فترة الإقامة بالمشفى , تخفيف حدة الألم التالي للجراحة و تقليل الانصباب المفصلي في الركبة, وتحسين إمكانية الاستناد على الطرف(السير) كما لوحظ انخفاض واضح في زمن الانقطاع عن العمل.